Characteristics of Mycobacterium tuberculosis PtpA interaction and activity on the alpha subunit of human mitochondrial trifunctional protein, a key enzyme of lipid metabolism - Margenat, Mariana; Betancour, Gabriela; Irving, Vivian; Costábile, Alicia; García-Cedrés, Tania; Portela, María Magdalena; Carrión, Federico; Herrera, Fernando E.; Villarino, Andrea (Frontiers in Cellular and Infection Microbiology, 2023)
During Mycobacterium tuberculosis (Mtb) infection, the virulence factor PtpA belonging to the protein tyrosine phosphatase family is delivered into the cytosol of the macrophage. PtpA interacts with numerous eukaryotic proteins modulating phagosome maturation, innate immune response, apoptosis, and potentially host-lipid metabolism, as previously reported by our group. In vitro, the human trifunctional protein enzyme (hTFP) is a bona fide PtpA substrate, a key enzyme of mitochondrial β-oxidation of long-chain fatty acids, containing two alpha and two beta subunits arranged in a tetramer structure. Interestingly, it has been described that the alpha subunit of hTFP (ECHA) is no longer detected in mitochondria during macrophage infection with the virulent Mtb H37Rv. To better understand if PtpA could be the bacterial factor responsible for this effect, in the present work, we studied in-depth the PtpA activity and interaction with hTFP. With this aim, we performed docking and in vitro dephosphorylation assays defining the P-Tyr-271 as the potential target of mycobacterial PtpA, a residue located in the helix-10 of hTFP, previously described as relevant for its mitochondrial membrane localization and activity. Phylogenetic analysis showed that Tyr-271 is absent in TFP of bacteria and is present in more complex eukaryotic organisms. This result suggests that this residue is a specific PtpA target, and its phosphorylation state is a way of regulating its subcellular localization. We also showed that phosphorylation of Tyr-271 can be catalyzed by Jak kinase. In addition, we found by molecular dynamics that PtpA and hTFP form a stable protein complex through the PtpA active site, and we determined the dissociation equilibrium constant. Finally, a detailed study of PtpA interaction with ubiquitin, a reported PtpA activator, showed that additional factors are required to explain a ubiquitin-mediated activation of PtpA. Altogether, our results provide further evidence supporting that PtpA could be the bacterial factor that dephosphorylates hTFP during infection, potentially affecting its mitochondrial localization or β-oxidation activity.